2014
DOI: 10.4236/oalib.1101031
|View full text |Cite
|
Sign up to set email alerts
|

Duodenogastric Reflux after Biliary Procedure

Abstract: Duodenogastric reflux (DGR) is a poorly understood gastrointestinal process that is defined as reflux of duodenal contents into the stomach. Therapeutic biliary procedures disrupt the function of the sphincter of Oddi. Patients are potential "bile refluxers". Methods: The present study was carried out to document the incidence and evaluate the clinical significance of DGR after cholecystectomy (n = 9) and choledochoduodenostomy (CDD) (n = 6). Duodenogastric reflux was quantified using continuous intravenous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The prevalence of bile reflux gastritis was (71.43 %) post-ERCP. Previous studies have shown that the prevalence of bile reflux after therapeutic biliary procedures was 60% (19).…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of bile reflux gastritis was (71.43 %) post-ERCP. Previous studies have shown that the prevalence of bile reflux after therapeutic biliary procedures was 60% (19).…”
Section: Discussionmentioning
confidence: 98%